Antimicrobial Activity of Lactic Acid Bacteria Isolated From Goat Meat against Various Pathogenic Bacteria - S, Elamathy (International Journal of Pharmaceutical & Biological Archive, 2012)
Antimicrobial Activity of Lactic Acid Bacteria Isolated From Goat Meat against Various Pathogenic Bacteria